ANALISIS PENYERAPAN TENAGA KERJA INDUSTRI KECIL DI 19 KABUPATEN/KOTA PROPINSI SUMATERA BARAT - Ariusni Ariusni; Mike Triani (Universitas Negeri Padang, 2013)
This study aimed to analyze the relationship between variables wage estimates, the value of production and the number of small industries to total workers absorbed in the small industry 19 districts/cities in West Sumatra. Results of panel regression model showed that there is no significant effect on wages caused by the rigidity of wages or salaries that balances inflexible employment so the impact will be an increase in unemployment in the county/city of West Sumatra Province. The production value has no significant effect on employment in the county/city of West Sumatra Province. This is due to the labor working with a low level of productivity of labor in which the ability to produce goods is limited due to the low skill level of each area. Number of small industry has significant effect on industrial employment of small industries in 19 districts/cities in West Sumatra Province. This suggests that increasing the number of small industries will have broad impact on employment in the regions of West Sumatra Province.